Cleavage of Catechol Monoalkyl Ethers by Aluminum Triiodide–Dimethyl Sulfoxide - Sang, Dayong; Tian, Juan; Tu, Xiaodong; He, Zhoujun; Yao, Ming (Synthesis, 2019)
Using eugenol and vanillin as model substrates, a practical method is developed for the cleavage o-hydroxyphenyl alkyl ethers. Aluminum oxide iodide (O=AlI), generated in situ from aluminum triiodide and dimethyl sulfoxide, is the reactive ether cleaving species. The method is applicable to catechol monoalkyl ethers as well as normal phenyl alkyl ethers for the removal of methyl, ethyl, isopropyl, and benzyl groups. A variety of functional groups such as alkenyl, allyl, amide, cyano, formyl, keto, nitro, and halogen are well tolerated under the optimum conditions. Partial hydrodebromination was observed during the demethylation of 4-bromoguaiacol, and was resolved using excess DMSO as an acid scavenger. This convenient and efficient procedure would be a practical tool for the preparation of catechols.
Keywords: acid scavenger; aluminum oxide iodide; demethylation; eugenol; hydrodebromination